A document delivery service for foreign scholarly journals: the experiences of South Korea. Issue 2 (16th May 2016) - Lee, Ji Won; Kim, Soojung
Abstract : Purpose: This study aims to describe the current status and usage trends of a new document delivery service (DDS) for foreign scholarly journals in Korea. Design/methodology/approach: Data were collected from 2010 to 2016 for the number of foreign journal subscriptions held by Foreign Research Information Centers (FRICs), number of FRIC DDS requests, the amount of government funds spent on the subscriptions, etc. Findings: There has been an increase in the number of foreign journal subscriptions and DDS transactions by FRICs, especially in the fields of science, technology and medicine. Originality/value: The DDS project in this study offers a useful example of collaboration between the government and academic libraries to provide research communities with foreign scholarly journals.